The complete chloroplast genome sequences of a wild diploid alfalfa Medicago edgeworthii (Leguminosae) - Tie Mei Wang; Kao Hui Xia; Cheng Jin (Mitochondrial DNA. Part B. Resources, 2020)
Medicago edgeworthii is a relatively unique species, which has the potential prospect to cross with M. sativa. In this study, we assembled the complete cp genome of M. edgeworthii using the Illumina sequencing data. The total genome is 122,442 bp in length and contains only one inverted repeat (IR) copy. The genome encodes 112 genes, including 76 protein-coding genes (PCGs), 32 tRNA genes, and 4 rRNA genes. Phylogenetic analysis using 11 cp genomes revealed the phylogenetic relationship of this species in Leguminosae.